ANALISIS KERJASAMA KELOMPOK TANI PEPAYA CALIFORNIA DENGAN HYPERMART LIPPO PLAZA KENDARI - Herlina, Herlina; Rianse, Usman; Nalefo, La (Fakultas Pertanian Universitas Halu Oleo, 2023)
The objective of this study is to analyze the cooperative pattern, advantages, and disadvantages of the California Papaya Farmer Group with Hypermart Lippo Plaza Kendari. The research utilized a descriptive method with a qualitative approach. The study's informants are California papaya farmers who have a cooperative relationship with Hypermart Lippo Plaza, intentionally selected based on predetermined criteria. Data were collected through observation, interviews, and documentation methods. Data were collected through an interview guide and analyzed using qualitative methods as described by Mills and Huberman, including field notes, information collection, information presentation, and conclusion drawing. The results indicate that the California papaya farmer group cooperated with Hypermart Lippo Plaza Kendari through a sub-contract partnership pattern. The cooperation pattern offers several advantages, including price and market certainty, production continuity, and higher product selling prices for farmers who participate. However, one major shortcoming of this pattern is that Hypermart Lippo Plaza Kendari does not distribute farming risks, meaning that the partner group bears all the risk.